Social-Emotional Learning in a Time of Chaos - Bond, John B. (International Dialogues on Education Journal, 2020)
Over the last generation public schools in the United States have strongly emphasized student achievement as measured by standardized tests. In this paper the role Social-Emotional Learning (SEL) can play in improving student success is emphasized. Research on SEL has shown that student achievement is positively affected by SEL programming. Yet, an argument continues over how the limited time in the classroom is used. As the world faces a pandemic during which students are often not attending school in person, their social-emotional health is of increased concern.